Employability : - Neugebauer, Jonh (Sage, 2016)
This books help you know about emloyer and education research, career case studies and using the book to meet the career challenge throught emloyability and employer's perspectives. For you Know barriers to emloyability to overcome. At the same time, help you can improve interpersonal skills.